Frontispiece: High‐precision isotopic analysis of essential mineral elements: capabilities as a diagnostic/prognostic tool (View 1/2021). Issue 1 (6th February 2021) - Vanhaecke, Frank; Costas‐Rodríguez, Marta
Abstract : For several essential mineral elements (metals such as Ca, Mg, Fe, Cu, Zn), it has been demonstrated in article number 20200094 by Frank Vanhaecke and his colleague that different body compartments may display different isotopic compositions and that disease conditions may alter the isotopic composition of that element in a biofluid and/or tissue. Multi‐collector ICP‐mass spectrometry (MC‐ICP‐MS) offers the precision required to reveal and quantify such differences in isotope ratios. As a result, high‐precision isotopic analysis shows promise as a diagnostic or prognostic tool. This review paper provides the background of such approach and sketches the state‐of‐the‐art.